Treatment Results of Patients Followed in Intensive Care Unit in Severe Maternal Morbidity Cases - Uslu Yuvaci, Hilal; Duzcan, Tuba; Akdemir, Nermin; Sever, Erman; Ozden, Selcuk; Cevrioglu, Arif Serhan; Unal, Orhan; Tozlu, Funda; Sayhan, Havva (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: The aim of this study was the evaluation of the characteristics and treatment results of women, who were brought to the intensive care unit due to severe obstetric morbidity, together with severe and acute complications in pregnancy. Study Design: Pregnant and puerperal women treated in the intensive care unit of a tertiary care center during two years of time were included in this study, and their files were scanned retrospectively. Patients’ demographic characteristics, length of stay, point of entry, neonatal results, birth statuses and modes of delivery, hemodynamic data, and histories were recorded. The qualitative data were evaluated by the Pearson Chi-squared, Fisher Freeman Halton, and Fisher’s Exact tests. Results: In the two-year period, 16,728 births occurred at our hospital. 68 cases among them were accompanied with severe maternal morbidity, and 2 maternal deaths were observed in our clinic. Of the cases, 58.8% (n=40) had severe hypertensive diseases, whereas 35.3% of the cases (n=24) had obstetric complications that developed due to bleeding. While 40% of the cases (n=16) with hypertension had severe pre-eclampsia, 35% of the cases (n=14) had eclampsia and 25% (n=10) had HELLP. Conclusions: The most important reasons for severe maternal morbidity are the complications related to obstetric bleeding and hypertensive diseases related to pregnancy. Early diagnosis of the obstetric complication risk factors is necessary for preventing maternal morbidity. Antenatal follow-ups and the births of high risk pregnancy patients should be performed in tertiary centers.